«E la natura ha dato al canto umano… una meravigliosa forza». Il fondo librettistico e gli aspetti musicali della Biblioteca Leopardi - Ciarlantini, Paola (Rivista Internazionale di Studi Leopardiani, 2022)
This paper focuses on the musical materials contained in the private library of the Leopardi House in Recanati, which I have been studying under the permission of the House holders since 1989. In particular, this paper focuses on the opera librettos contained in the Leopardi House library: 100 of the analysed librettos are preserved in the Fondo dell’Alcova («Collection of the Bed Chamber»), whereas 25 are preserved in other collections within the library of which I give a detailed list. Through analysing the contents of the librettos found in the Leopardi House library, this paper seeks to shed light on the activities and on the personal and cultural relations between the Leopardi family and its contemporaries between the 18th and the 19th centuries. Special focus is given to the figures of Paolina and Luigi Leopardi, siblings of the poet Giacomo, who showed the greatest interest in music within the Leopardi family. In this paper’s Appendix, I offer a brief description of the Collection of musical materials of the Centro Nazionale di Studi Leopardiani (“National Centre of Leopardi Studies”) (CNSL), which was founded in the 2nd centenary of Giacomo Leopardi’s birth (1998).